The Effect of Dividend Policy on Stock Prices of LQ-45 Company in the Indonesia Stock Exchange - Wella Kurnia; Muhammad Subhan; Defri Ahmad (Rangkiang Mathematics Journal, 2022)
An investment choice is a dividend policy. Either the company's gains will be given to shareholders as dividends, or they will be maintained as earnings to finance future investments. The dividend payout ratio and dividend yield are the dividend policy indicators utilised in this study. This study seeks to examine the impact of dividend payout ratio (DPR) and dividend yield on the stock prices of LQ-45 businesses listed on the Indonesia Stock Exchange. Multiple linear regression analysis is employed. The results indicated that the dividend payout ratio and dividend yield had no effect on the stock prices of the LQ-45 companies listed on the Indonesia Stock Exchange. According to multiple linear regression analysis results, obtained sig value (0.606) > α (0.05).